0578 Sleep Disordered Breathing and Functioning in Activities of Daily Living in Patients with Spinal Cord Injury or Disease. (12th April 2019) - Arvai, Kelsey L; Kelly, Monica R; Mitchell, Michael N; Vaughan, Sarah E; Chowdhuri, Susmita; Salloum, Anan; Henzel, M Kristi; Sankari, Abdulghani; Martin, Jennifer L; Badr, M Safwan
Abstract: Introduction: Patients with spinal cord injury or disease (SCI/D) often experience difficulties with activities of daily living (ADLs). Sleep disordered breathing (SDB) is also associated with poor functioning in some populations, but has not been considered as a contributing factors to functional disability in SCI/D patients. Our objective was to examine the impact of SDB severity on ADLS in SCI/D patients. Methods: 57 Veterans (average age=58.53 ± 10.69; range=34-79 years; 91% male, average BMI=27.89 ± 5.72) with SCI/D completed baseline questionnaires as part of a larger study. 46 completed in-laboratory polysomnography (PSG) to measure apnea-hypopnea index (AHI). Separate nested regression models predicted the total and each subscale of the Spinal Cord Independence Measure III [SCIM; 1) self-care, 2)respiration and sphincter management, 3) mobility]. Block 1 included demographic covariates (age, gender, race, education, marital status, BMI. Block 2 included level of injury (cervical vs. thoracic or below). Block 3 included AHI. Results: The mean AHI=25.26 ± 21.81 (range=1.6-81.5), and 56.5% had AHI>15. Overall models were not significant for SCIM respiration/sphincter management or mobility subscales. All variables in Blocks 1-3 were jointly associated with SCIM total (R 2 =33%, adjusted R 2 =0.19) and self-care subscale (R 2 =35%, adjusted R 2 =0.21) scores. Block 1 did not explain a significant proportion of variance in the SCIM total score (p=.54) or the self-care subscale (p=.41), Level of injury did explain significant variance in SCIM total (p=.01), but not in the self-care subscale scores (p=.09). Block 3 explained an additional 8.1% of variance in SCIM total (p=.04) and 14.9% of variance in SCIM self-care subscale (p=.01) after accounting for Blocks 1 and 2. Conclusion: Sleep disordered breathing was significantly associated with overall functioning in ADLs among SCI/D patients, even after accounting for demographics and level of injury. Studies on optimized treatment of SDB in these patients has the potential to improve functioning and independence. Support (If Any): VA Rehabilitation Research and Development Service (RX002116; PI Badr)